Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376285
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Software Developers' Focused Work on Window-Based Desktops

Abstract: Software developers, like other information workers, continuously switch tasks and applications to complete their work on their computer. Given the high fragmentation and complexity of their work, staying focused on the relevant pieces of information can become quite challenging in today's windowbased environments, especially with the ever increasing monitor screen-size. To support developers in staying focused, we conducted a formative study with 18 professionals in which we examined their computer based and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In the literature there are many examples of approaches taken to facilitate or encourage focused work. Such approaches include designing interfaces with minimal visual clutter to support focused work [29], blocking or reducing websites unrelated to work [19,38], and supporting self-tracking to reflect on time spent and minimize distractions [15]. Additionally, there has been an increase in the development of time management tools that promote continuous work [18,32].…”
Section: Flow and Focused Workmentioning
confidence: 99%
“…In the literature there are many examples of approaches taken to facilitate or encourage focused work. Such approaches include designing interfaces with minimal visual clutter to support focused work [29], blocking or reducing websites unrelated to work [19,38], and supporting self-tracking to reflect on time spent and minimize distractions [15]. Additionally, there has been an increase in the development of time management tools that promote continuous work [18,32].…”
Section: Flow and Focused Workmentioning
confidence: 99%
“…For example, Minelli et al (2015a) found that developers spent 14% of their time "fiddling with the UI" to organize windows within their IDEs. With the addition of eye tracking, Pilzer et al (2020) found that developers switched between windows every 16 seconds. Developers need to open and switch between numerous windows because a single code feature or concern is often spread across multiple artifacts each requiring its own dedicated window (Robillard and Murphy, 2007).…”
Section: Tracking Ide Interactionsmentioning
confidence: 99%